Bi-allelic variation of FANCJ (BRIP1) identified in premature ovarian insufficiency - Chunmei Zhang; Ting Guo; Xin Liang; Yingying Qin; Anmiao Sun; Xinmiao He; Mengchun Hu; Hongyuan Liu; Xiaowei Wu; Manting Yang; Runxin Yao; Shidou Zhao; et al. (Gynecology and Obstetrics Clinical Medicine)
Objective Premature ovarian insufficiency (POI) is defined as the depletion of ovarian function before 40 years of age, affecting approximately 3.7% of women in their reproductive age worldwide. Previous studies revealed several genes involved in the Fanconi anaemia (FA) pathway participate in the pathogenesis of POI, such as FANCA and FANCM. FA pathway maintains rapid proliferation in the developing primordial germ cells by deregulating transcription-replication conflicts, which is crucial for the establishment of sufficient ovarian reserve. FANCJ encodes a DNA helicase located downstream of the FA pathway promoting DNA damage repair and cell proliferation. Recently, two heterozygous FANCJ missense variants have been reported in patients with POI, suggesting haploinsufficiency of FANCJ participates in the pathogenesis of the disease. In this study, to further explore the contribution of FANCJ variants in POI, we reported a rare homozygous FANCJ start-loss variation in one patient with POI and illustrated its pathogenicity by in vitro functional studies.Methods The loss-of-function (LoF) variants of FANCJ were screened in our internal whole-exome sequencing (WES) database of POI. Sanger sequencing and WES analysis were employed on the proband and the patient’s family members to illustrate the origin of the bi-allelic variant. Cycloheximide chase assay was performed to demonstrate the impact of the variant on the protein stability of FANCJ. Protein ubiquitination assay was performed to confirm the accelerated degradation pathway of FANCJ protein.Results Through the variation screening, a bi-allelic variant of FANCJ (NM_032043.3:c.1A>G, p.Met1Val) was identified in one case. The functional study showed that the start-loss variant affected FANCJ protein stability by accelerated protein degradation through the ubiquitin-proteasome pathway.Conclusion Our findings provide further genetic evidence of the FANCJ variant participating in the pathogenesis of POI, expand the inherited mode and highlight the essential role of the FA pathway in maintaining ovarian function.